Artificial intelligence research and development : proceedings of the 13th International Conference of the Catalan Association for Artificial Intelligence - Catalonian Conference on AI (13th : 2010 : Espluga de Francol,̕ Spain); Alqužar, Ren; Moreno, Antonio; Aguilar-Martin, J. (Amsterdam ; Washington, DC : IOS Press)
Includes bibliographical references and indexes